Validation of the blocked force method for various boundary conditions for automotive source characterization. (15th January 2016) - Lennström, David; Olsson, Magnus; Wullens, Frédéric; Nykänen, Arne
Abstract: Vibro-acoustic source characterization is an essential task in vehicle development to enable prediction of receiver response. For structure-borne noise, the interface forces in multiple degrees of freedom due to internal loads are often quantified for root cause analyses in a single system assembly, as in transfer path analysis (TPA). However, for a reliable prognosis of the acoustic performance of a known component such as a motor or pump, a receiver-independent source characterization is required, and the method of acquiring blocked forces from in-situ measurements has been shown to be a preferred technique for such purposes. The benefits of the method are the characterization of the intrinsic properties of the source and the possibilities of measuring the component attached to receivers with varying dynamic properties. There is to date a limited number of validation cases where blocked forces from in-situ measurements are acquired for automotive source–receiver assemblies. In this study the blocked forces of a vacuum pump in nine degrees of freedom were determined when connected to a bracket whose boundary conditions were modified in order to achieve four assemblies with different source/receiver dynamic properties. The results show that the blocked forces are transferable, i.e. the receiver response in one assembly was predicted in a wide frequency range by combining source–receiver transfer functions of that assembly with blocked forces estimated in another assembly. Furthermore, an in-situ blocked force TPA was applied to a double-isolated complete vehicle source–receiver case of an electric rear axle drive with interior compartment sound pressure as target. The reconstructed magnetic tonal harmonics agreed with the measured target response in the frequency range 50–500 Hz, which further motivates the use of the blocked force principles for TPA and source requirements specifications.